KHALED HOSSEINI’S WORLD VIEW ON AFGHANISTAN SOCIETY DEPICTED IN A THOUSAND SPLENDID SUNS - Efrilia Efrilia; Dwi Budi Setiawan (Linguistics and Literature Students' Journal, 2020)
Culture is the complex whole that man has acquired as a member of society. The culture shows the result of the behavior and habits of the societies of its place. Khaled Hosseini through his novel tries to extend his thought based on his view over the sociological problem which exists in Afghanistan. This investigation aims to explain the author's world view which focuses on a novel entitled A Thousand Splendid Suns by Khaled Hosseini. The setting of the novel is in Afghanistan from the 1960s until the early 2000s. Through this novel, Khaled Hosseini describes the Sociological issues which happen in Afghanistan at that time. In analyzing the data, the author uses a descriptive qualitative method and focused on Lucien Goldmann's theory of genetic structuralism. The result of this research shows that there are some problems within Afghan society such as (1) the education system, (2) marriage, and (3) domestic violence.